Prevalence and determinants of diabetic patience readmissions at Seshego District Hospital, Capricorn District, Limpopo Province, South Africa - Maremane, Ramokone Cilvia (My University, 2023)
Background: Diabetes mellitus is a public health concern epidemiolocally and economically. The rates of readmission in diabetic patients are reported to be high as compared to non-diabetic patients. With many factors contributing to readmission of diabetic patients, there are preventable and non-preventable factors. A good understanding of the causes and risk factors associated with readmission is necessary in order to prevent/reduce readmission rates. Methods: A retrospective descriptive study was conducted which followed a quantitative approach. This study used secondary data from patient clinical records from the paediatrics, male, female and TB ward in Seshego Hospital. The data was analysed using STATA and descriptive statistical analysis was undertaken to identify frequencies and percentages of answers to the research questions. For logistic regression, the independent variables were socio-demographic factors such as age, gender, marital status, race, and employment status. The dependent variable was the diagnosis of diabetes and its readmission into the hospital. The statistical significance of the relationships between the selected variables was determined using the t-test. The level of significance was set at 0.05 and 95% confidence interval will be used to judge statistical significance. Results: The prevalence of diabetic patients’ readmission is very high in the current study. The prevalence of readmission of diabetes increased with increasing age both in males and females patients. The prevalence increased from 6.7% in age group between 18 and 29 years followed by 10%, 13.3% and 70% in males aged 30 – 49 years, 50 – 59 years and above 60 years respectively. The study showed that employment status, number of medication and type of medication are significantly associated with readmission while those high white blood cells count, comorbidities, level of education and marital status were more likely to be readmitted, although they were not statistically significant. Conclusion: The study revealed high prevalence of readmission of diabetic patients and showed that employment status, number of medication and type of medication are significantly associated with readmission while those with high white blood cells count, comorbidities, level of education and marital status were more likely to be readmitted, although they were not statistically significant. Recommendations: the current study revealed that there is a need for a primary data to further investigate the causes of readmission in diabetic patients for effective intervention in order to reduce the rates of readmission.
Thesis (MPH.) -- University of Limpopo, 2023
Keywords: Determinants; Diabetes mellitus; Prevalence; Readmission; Diabetes; Diabetes -- Treatment; Health facilities; Diabetics -- Care -- South Africa -- Limpopo